PENERAPAN PERMAINAN TEMBAK IKAN UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR MELEMPAR PADA SISWA KELAS II SD - IRWAN BUDI CAHYONO (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
This study aims to determine the application of the game "Shoot Fish" in improving learning outcomes of basic throwing motions. This research is a classroom action research. The survey was conducted in two cycles. Each cycle consists of two meetings covering the stages of planning, implementing actions, observing and reflecting. The research subjects were second grade students of SDN 013 Tana Tidung, totaling 20 students. Sources of data used are observations, tests, and student learning outcomes documents. For data analysis using quantitative descriptive analysis techniques. The results showed that the results of learning the basic throwing motion of second grade students of SDN 013 Tana Tidung increased after the application of the Fish Shoot game method. These results are indicated by an increase in student learning outcomes in each cycle. The improvement of student learning outcomes is seen from two aspects, namely based on students' cognitive and psychomotor. Students' cognitive learning outcomes have increased as indicated by the increase in the average value of 73,00 in the first cycle and increased to 87.00 in the second cycle and being able to pass the KKM value 75. ABSTRAKPenelitian ini bertujuan untuk mengetahui penerapan permainan “Tembak Ikan” dalam peningkatan hasil belajar gerak dasar melempar. Penelitian ini merupakan penelitian tindakan kelas. Survei dilakukan dalam dua siklus. Setiap siklus terdiri dari dua pertemuan meliputi tahap perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subjek penelitian adalah siswa kelas II SDN 013 Tana Tidung yang berjumlah 20 siswa. Sumber data yang digunakan adalah observasi, tes, dan dokumen hasil belajar siswa. Untuk analisis data menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa hasil belajar gerak dasar melempar siswa kelas II SDN 013 Tana Tidung mengalami peningkatan setelah penerapan metode permaianan Tembak Ikan. Hasil ini ditunjukkan dengan adanya peningkatan hasil belajar siswa pada setiap siklusnya. Peningkatan hasil belajar siswa dilihat dari dua aspek yaitu berdasarkan kognitif siswa dan psikomotor. Hasil observasi psikomotor siswa mengalami peningkatan ditunjukkan dengan meningkatnya nilai rata-rata 73 pada siklus I dan meningkat menjadi 87 pada siklus II dan mampu melewati nilai KKM ? 75.